Analysis of the factors affecting pain level during K-wire removal among pediatric elbow fractures. Issue 2 (20th March 2023) - Zhamilov, Vadym; Turgut, Ali; Reisoglu, Ali; Basa, Can Doruk; Kacmaz, İsmail Eralp and Kazimoglu, Cemal
Abstract : Our aim was, to analyze the reasons for possible increased pain during the removal of the Kirschner wires from the elbows of children. From February 2021 to December 2021, 573 patients with elbow fractures were treated. In total, 150 patients were analyzed prospectively. No action was taken to reduce pain during the removal of Kirschner wires. The pain status of the patients was evaluated according to the Wong-Baker FACES Pain Rating scoring system (WBAS), the Numeric Rating Scale (NRS) for the pain system and the pulse and oxygen saturation measured by the pulse oximeter on the finger. Measurements were performed before, during, immediately after and 30 min after the procedure. There were 119 patients with a diagnosis of supracondylar humerus fracture and 31 patients with a diagnosis of lateral condyle fracture. The mean age of treated patients was 7.1 years (1–15 years). Of the patients, 93 were boys and 57 were girls. In the measurements made according to the sex difference, it was determined that there was a statistically significant increase in the WBAS scores measured both before the procedure ( P = 0.032) and during the removal ( P = 0.017), and also in the pulse measurements taken 30 min after the removal in girls ( P = 0.034). A statistically significant difference was found in both the WBAS score during removal ( P = 0.025) and the NRS scores 30 min later ( P = 0.048) in the procedures performed on the right elbow. We found a statistically significant increase in the pain parameters we evaluated in girls, right extremity fractures, the group over 8 years old and when both parents were with the child during the K-wire removal procedure. In light of these findings, physicians should consider the above-mentioned conditions before starting the procedure to ensure a less painful and positive experience.